2004
DOI: 10.1093/carcin/bgh189
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of aminophenylnorharman, a possible novel endogenous mutagen, formed from norharman and aniline, in F344 rats

Abstract: A novel mutagenic compound, 9-(4'-aminophenyl)-9H- pyrido[3,4-b]indole (aminophenylnorharman, APNH), is shown to be formed by the in vitro enzymatic reaction of 9H-pyrido[3,4-b]indole (norharman) and aniline. APNH generates DNA adducts (dG-C8-APNH), and is potently genotoxic to bacteria and mammalian cells. APNH has also been demonstrated to be formed in vivo from norharman and aniline, and suggested to be a new type of endogenous mutagenic compound. To determine its carcinogenic activity, long-term administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…13). However, APNH is a more potent carcinogen than Trp-P-1 and MeIQx (10,28), so that the risk of human cancer might be similar. To understand the role of APNH in human cancer development, studies for APNH levels in human urine samples, which are balanced by age and gender, APNH metabolism, and other factors that affect APNH levels, will be required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13). However, APNH is a more potent carcinogen than Trp-P-1 and MeIQx (10,28), so that the risk of human cancer might be similar. To understand the role of APNH in human cancer development, studies for APNH levels in human urine samples, which are balanced by age and gender, APNH metabolism, and other factors that affect APNH levels, will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenic activity of APNH in S. typhimurium strains proved comparable with those of 2-amino-3,8-dimethylimidazo [4,5-f]quinoxaline (MeIQx) and 3-amino-1-methyl-5H-pyrido [4,3-b] indole (Trp-P-2), food-borne carcinogenic heterocyclic amines (5,9). In a long-term carcinogenicity experiment using F344 rats, APNH induced tumors in the liver, colon, thyroid, hematopoietic systems, and clitoral gland (10). To investigate the in vivo formation of APNH from norharman and aniline, we analyzed APNH in urine of rats and detected the compound only in animals fed norharman and aniline and not in the controls or with either norharman or aniline alone (11).…”
Section: Introductionmentioning
confidence: 99%
“…APNH formed DNA adducts in the liver and induced HCC in F344 rats. 17 However, the mice received with APNH/DSS had no liver tumors in this study. These differences in the liver carcinogenicity of APNH may be due to the differences in the experimental protocol.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, the location and mutation pattern were slightly different from a report documenting that the b-catenin gene mutations of rat colon tumors induced by APNH; G:C to A:T transition at codon 34 was predominant. 17 Masumura et al has also reported that PhIP…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation